Epiphytic diatoms as indicators of ecological condition in New Zealand's lowland wetlands. Issue 4 (2nd October 2017) - Kilroy, C.; Suren, A. M.; Wech, J. A.; Lambert, P.; Sorrell, B. K.
ABSTRACT: The condition of New Zealand's remnant wetlands has been documented by landscape-scale assessments such as the Index of Ecological Integrity and Wetland Condition Index. We explored the potential for microscopic aquatic biota (epiphytic diatoms) to provide complementary information about wetland condition using data from 77 lowland sites (mainly palustrine swamps) with circumneutral pH. In the South Island, correspondence between diatoms and wetland indices or water quality was weak. In the North Island, conductivity and total dissolved nitrogen (TDN) together explained 49% of the variance in assemblage composition and several diatom genera were indicative of high or low conductivity, dissolved phosphorus and TDN. Changes in these water quality variables may trigger changes in wetland condition, which are eventually reflected by the landscape-scale indices. Diatoms respond rapidly to water quality changes suggesting potential for diatom indicator taxa to provide early warning of wetland degradation or to track restoration.